نشاط منظمة الوحدة الإفريقية والقانون الدولي في ضمان التعاون الأمني في القارة الإفريقية /1963-1993/ - زينب سعد (Latakia University Journal - Economic and Legal Sciences Series, 2018)
Until the middle of the 20th century, Africa was the scene of colonial competition. A number of European countries controlled and exploited its various resources. The beginning of the 1960s witnessed the independence of 15 countries. This number increased until most of the continent became independent Since the independence of the country of the African continent, there have been many attempts to unite and unite between these countries, until the Organization of African Unity emerged as a regional organization, working within the African continent to renounce African differences, and to end the blocs and shorten the activities of the organizations that existed, on specific areas of economic, technical or cultural. The establishment of an Organization of the African Unity was announced on June 25, 1963, through the resolutions adopted by the Addis Ababa Conference, which resulted in the Charter of the Organization of African Unity, which approved the Constitution of the Organization: 1- the liberation of the continent from colonialism 2- Elimination of underdevelopment in all its forms 3- Consolidation of African solidarity 4-Upgrading the continent to the status it deserves in the field of international decision-making The Charter of the African Unity Organization includes a balanced human rights document in which the objectives and principles have been adopted and the regulatory bodies. The objectives of the Organization by all standards are consistent with international law, as well as with the Charter of the United Nations, as it calls for the maintenance and strengthening of international peace and security. In the recommendation of the United Nations General 5/12/1986 Assembly on the establishment of a global security system "It was emphasized that the system of security cooperation, as stipulated in the Charter of the International Organization and continues to be an essential means of maintaining international peace and security" Article 1 The UN Security Council, in its recommendation of 30 December 1964, recognized that the Organization of African Unity (OAU), a regional organization under Article 52 of the Charter of the United Nations, would assist in the peaceful resolution of disputes affecting international peace and security on the African continent. Is the guarantee of security on the African continent, and this is directly linked to the process of applying the primacy of the unitary integration on the continent. Without this application, the security system will be collapsible and this shows the need to add a chapter of the Organization of African Unity Charter on the issue of security and its security mechanism. ظلت إفريقية حتى منتصف القرن العشرين، مسرحاً للتنافس الاستعماري لعدد من الدول الأوروبية، التي سيطرت عليها واستغلت مواردها المختلفة، وشهد بداية عقد الستينات استقلال 15 دولة، ثم ازداد هذا العدد إلى أن استقلت معظم دول القارة. منذ استقلال بلاد القارة الإفريقية، تعددت محاولات التجمع والوحدة بين هذه الدول، حتى ظهرت منظمة الوحدة الإفريقية كمنظمة إقليمية، تعمل في إطار القارة الإفريقية على نبذ الخلافات الإفريقية وإنهاء التكتلات، واقتصر نشاط المنظمات التي كانت قائمة، على مجالات محددة اقتصادية أو فنية أو ثقافية. لقد تم الإعلان عن إنشاء منظمة الوحدة الإفريقية في 25 حزيران 1963، من خلال القرارات التي صدرت عن مؤتمر أديس أبابا، حيث انبثق عنها ميثاق منظمة الوحدة الإفريقية الذي أقر دستور المنظمة، وتم تحديد الأهداف التالية: 1- تحرير القارة نهائياً من الاستعمار. 2- القضاء على التخلف بجميع أشكاله. 3- توطيد دعائم التضامن الإفريقي. 4- الارتقاء بالقارة إلى المكانة التي تليق بها على ساحة صنع القرارات الدولية ... الخ. ميثاق منظمة الوحدة الإفريقية، يتضمن وثيقة حقوقية توازنية، والتي فيها تم إقرار الأهداف والمبادئ والهيئات التنظيمية. أهداف المنظمة حسب كل المقاييس تتفق مع القانون الدولي، وكذلك مع ميثاق الأمم المتحدة، حيث إنها تدعو لصون وتعزيز الأمن والسلم الدوليين، ففي توصية الدورة العامة للأمم المتحدة 5/12/1986 م حول إنشاء نظام أمن عالمي "تم التأكيد، على أن نظام التعاون الأمني، نص عليه في ميثاق المنظمة الدولية، ولا يزال يشكل وسيلة أساسية في المحافظة على الأمن والسلم العالميين". المادة 1. أما مجلس الأمن الدولي في توصيته 30/12/1964، اعترف بأن منظمة الوحدة الإفريقية، منظمة إقليمية حسب المادة /52/ من ميثاق الأمم المتحدة، وهذه المنظمة ستساعد في حل النزاعات بالطرق السلمية، التي تؤثر على الأمن والسلم العالميين في القارة الإفريقية. إن الهدف الأساسي هو ضمان الأمن في القارة الإفريقية، وهو مرتبط بشكل مباشر بعملية تطبيق أولوية التكامل الوحدوي في القارة، وبدون هذا التطبيق، يبقى نظام الأمن قابلاً للانهيار، وهذا يبين ضرورة إضافة فصل لميثاق منظمة الوحدة الإفريقية، حول مسألة الأمن وآلية ضماناته، وضرورة إقرار تشكيل قوات أمن إفريقية.